It is currently 15 Dec 2017, 23:30

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If 0.0015*10^m/0.03*10^k=5*10^7, then m - k =

Author Message
TAGS:

### Hide Tags

Manager
Joined: 02 Dec 2012
Posts: 178

Kudos [?]: 3655 [0], given: 0

If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

31 Dec 2012, 04:41
22
This post was
BOOKMARKED
00:00

Difficulty:

25% (medium)

Question Stats:

67% (01:07) correct 33% (01:21) wrong based on 1156 sessions

### HideShow timer Statistics

If $$\frac{0.0015*10^m}{0.03*10^k}=5*10^7$$, then m - k =

(A) 9
(B) 8
(C) 7
(D) 6
(E) 5
[Reveal] Spoiler: OA

Kudos [?]: 3655 [0], given: 0

Math Expert
Joined: 02 Sep 2009
Posts: 42622

Kudos [?]: 135778 [6], given: 12711

Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

31 Dec 2012, 04:45
6
KUDOS
Expert's post
5
This post was
BOOKMARKED
If $$\frac{0.0015*10^m}{0.03*10^k}=5*10^7$$, then m - k =

(A) 9
(B) 8
(C) 7
(D) 6
(E) 5

$$\frac{0.0015*10^m}{0.03*10^k}=5*10^7$$;

$$\frac{15*10^{-4}*10^m}{3*10^{-2}*10^k}=5*10^7$$;

$$5*\frac{10^{m-4}}{10^{k-2}}=5*10^7$$;

$$10^{(m-4)-(k-2)}=10^7$$;

$$(m-4)-(k-2)=7$$;

$$m-k=9$$.

_________________

Kudos [?]: 135778 [6], given: 12711

Intern
Joined: 21 Mar 2009
Posts: 20

Kudos [?]: 27 [0], given: 0

Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

31 Dec 2012, 06:24
If $$\frac{0.0015*10^m}{0.03*10^k}=5*10^7$$, then m - k =

(A) 9
(B) 8
(C) 7
(D) 6
(E) 5

Rearrange the decimals : (15*10^-4*10^m)/(3*10^-2*10^k) = 5*10^7

After adjusting and cancelling 5 from each side : 10^(m-k-2) = 10^7
=> m-k-2=7 => m-k = 9

Kudos [?]: 27 [0], given: 0

Manager
Joined: 18 Oct 2011
Posts: 89

Kudos [?]: 97 [0], given: 0

Location: United States
Concentration: Entrepreneurship, Marketing
GMAT Date: 01-30-2013
GPA: 3.3
Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

03 Jan 2013, 12:49
rewrite the expression like this:

15(10)^-4 (10)^m / 3(10)^-2 (10)^k = 5(10)^7

When you simplify the expression you are left with: (10)^m / (10)^k = 10^9

Therefore m-k = 9

Kudos [?]: 97 [0], given: 0

Manager
Joined: 30 Jun 2012
Posts: 83

Kudos [?]: 161 [0], given: 16

Location: United States
GMAT 1: 510 Q34 V28
GMAT 2: 580 Q35 V35
GMAT 3: 640 Q34 V44
GMAT 4: 690 Q43 V42
GPA: 3.61
WE: Education (Education)
Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

14 Jul 2013, 14:50
I solved this question by cross multiplying.

15*10^-4m=15*10^-14k
-4m-14k=0
-4(7)-14(-2)=0
-28+28=0
m-k
7-(-2)= 9

sambam wrote:
rewrite the expression like this:

15(10)^-4 (10)^m / 3(10)^-2 (10)^k = 5(10)^7

When you simplify the expression you are left with: (10)^m / (10)^k = 10^9

Therefore m-k = 9

Kudos [?]: 161 [0], given: 16

Intern
Joined: 23 Mar 2011
Posts: 29

Kudos [?]: 4 [1], given: 9

Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

26 Jul 2013, 22:11
1
KUDOS
josemnz83 wrote:
I solved this question by cross multiplying.

15*10^-4m=15*10^-14k
-4m-14k=0
-4(7)-14(-2)=0
-28+28=0
m-k
7-(-2)= 9

Hello josemnz84 - I was looking at the alternate ways to solve this problem and I don't quite understand what you did here. Can you please explain? Specifically how did you get $$10^{-14k}$$. I feel this is incorrect, but please correct me if my calculations are off.

If you want to cross multiply, the problem would be done this way:

$$\frac{15*10^{-4 + m}}{3*10^{-2+k}} = 5*10^7$$

$$15*10^{-4 + m}=15*10^{5 + k}$$ - when you multiple powers of 10, you multiply the whole numbers and add the powers of 10 (you seemed to have multiplied the exponents rather than adding to get 10^-14 in your answer). See this: http://www.dummies.com/how-to/content/m ... ation.html

After cancelling out the "15 x 10^" (essentially 10^1) from both sides, you are left with:

$$-4 + m = 5 + k$$

$$m - k = 5 + 4$$

$$m - k = 9$$

~ Im2bz2p345

Kudos [?]: 4 [1], given: 9

Intern
Joined: 07 Sep 2013
Posts: 3

Kudos [?]: 1 [0], given: 0

plz help in solving this!! [#permalink]

### Show Tags

25 Oct 2013, 22:27
if (0.0015 . 10)^m/0.03 . 10^k = 5 . 10^7, then (m-k) =

a. 9
b.8
c.7
d.6
e.5

Kudos [?]: 1 [0], given: 0

Math Expert
Joined: 02 Sep 2009
Posts: 42622

Kudos [?]: 135778 [0], given: 12711

Re: plz help in solving this!! [#permalink]

### Show Tags

26 Oct 2013, 02:20
krithikaram89 wrote:
if (0.0015 . 10)^m/0.03 . 10^k = 5 . 10^7, then (m-k) =

a. 9
b.8
c.7
d.6
e.5

Merging similar topics. Please refer to the solutions above.

P.S. All OG13 questions with solutions are here: the-official-guide-quantitative-question-directory-143450.html
_________________

Kudos [?]: 135778 [0], given: 12711

SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1849

Kudos [?]: 2792 [1], given: 193

Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

26 Feb 2014, 01:42
1
KUDOS
Removing decimal point & solving ahead,

5 . 10^(m+2-4-k) = 5 . 10^7

Equating , m-k = 9 = Answer = A
_________________

Kindly press "+1 Kudos" to appreciate

Kudos [?]: 2792 [1], given: 193

Non-Human User
Joined: 09 Sep 2013
Posts: 14826

Kudos [?]: 288 [0], given: 0

Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

13 Mar 2015, 08:44
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Kudos [?]: 288 [0], given: 0

Non-Human User
Joined: 09 Sep 2013
Posts: 14826

Kudos [?]: 288 [0], given: 0

Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

10 May 2016, 05:39
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Kudos [?]: 288 [0], given: 0

Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 1945

Kudos [?]: 1021 [1], given: 3

Location: United States (CA)
Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

10 May 2016, 06:11
1
KUDOS
Expert's post
If $$\frac{0.0015*10^m}{0.03*10^k}=5*10^7$$, then m - k =

(A) 9
(B) 8
(C) 7
(D) 6
(E) 5

We start by simplifying the numerator and denominator of the given fraction. First, we simplify the numerator:

(0.0015)(10^m)

It will be helpful to convert 0.0015 to an integer. To do so we must move the decimal point in 0.0015 four places to the right. Since we are making 0.0015 larger by four decimal places we must make 10^m, smaller by four decimal places. Thus, 10^m now becomes 10^(m-4). Thus, the numerator becomes (15)(10^(m-4)).

Next we can simplify the denominator:

(0.03)(10^k)

It will be helpful to convert 0.03 to an integer. To do so we must move the decimal point in 0.03 two places to the right. Since we are making 0.03 larger by two decimal places we must make 10^k, smaller by two decimal places. Thus, 10^k now becomes 10^(k-2). The denominator can thus be re-expressed as (3)(10^(k-2)).

So now we are left with:

[(15)(10^(m-4))]/[(3)(10^(k-2))] = 5(10^7)

Dividing 15 by 3 on the left hand side of the equation, we have 15/3 = 5. Recall that when we divide powers of like bases, we subtract the exponents, so 10^(m-4)/10^(k-2) =
10^((m-4) – (k-2)) = 10^(m-k-2). Therefore, we have

5(10^(m-k-2)) = (5)(10^7)

5 will cancel out from both sides of the equation, leaving us with:

10^(m-k-2)=10^7

Because we are left with a base of 10 on both the right-hand side and the left-hand side of the equation, we can drop the base and set the exponents equal and hence determine the value of m – k:

m – k – 2 = 7

m – k = 9

_________________

Scott Woodbury-Stewart
Founder and CEO

GMAT Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

Kudos [?]: 1021 [1], given: 3

SVP
Joined: 11 Sep 2015
Posts: 1913

Kudos [?]: 2759 [1], given: 364

Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k = [#permalink]

### Show Tags

30 Nov 2016, 16:56
1
KUDOS
Expert's post
Top Contributor
If $$\frac{0.0015*10^m}{0.03*10^k}=5*10^7$$, then m - k =

(A) 9
(B) 8
(C) 7
(D) 6
(E) 5

Another approach is to assign k a "nice" value.

Let's see what happens when k = 0

We get: (0.0015 x 10^m) / (0.03 x 10^0) = 5 x 10^7

Simplify: (0.0015 x 10^m) / (0.03 x 1) = 5 x 10^7

Simplify: (0.0015 x 10^m) / (0.03) = 5 x 10^7

Multiply both sides by 0.03 to get: 0.0015 x 10^m = 0.15 x 10^7

Eliminate blue decimals by multiplying both sides by 10,000 to get: 15 x 10^m = 1500 x 10^7

Divide both sides by 15 to get: 1 x 10^m = 100 x 10^7

Rewrite 100 as 10^2: 1 x 10^m = 10^2 x 10^7

Simplify: 10^m = 10^9

So, m = 9

In other words, when k = 0, m = 9
So, m - k = 9 - 0 = 9

Cheers,
Brent
_________________

Brent Hanneson – Founder of gmatprepnow.com

Kudos [?]: 2759 [1], given: 364

Re: If 0.0015*10^m/0.03*10^k=5*10^7, then m - k =   [#permalink] 30 Nov 2016, 16:56
Display posts from previous: Sort by